Healthcare waste management in district hospitals of Madhesh province: A key stakeholder’s perspective - Patel, Jot Narayan; Upadhyay, Shambhu Kumar; Rajbhandari, Ajay (Journal of Ayurveda Campus, 2024)
Background: Healthcare waste is special waste produced in healthcare institutions, including hospitals. Healthcare waste management guideline adherence was low (16.3%) in Kenya. Nearly half (49.2%) of healthcare waste handlers had low knowledge of healthcare waste management, and 43.0% had negative attitudes toward it. In a sub-regional hospital, all healthcare waste management handlers were injured in a year; among them, 42.0% were injured less than 5 times. It contains a high potential for infection and injuries. Till the commencement of this study, published evidence on adherence to healthcare waste management guidelines 2014 in Madhesh province was not found. The study aimed to assess the adherence to healthcare waste management practices and knowledge among waste handlers at the government district hospitals of Madhesh province, Nepal. Materials and Methods: A cross-sectional qualitative method study was employed to interview ten key stakeholders from ten government district/level hospitals in Madhesh province with key informant interview guidelines for key stakeholders. A thematic analysis was done using R-Package Qualitative Data Analysis (RQDA) version R-3.6.1. Results and Discussion: The government of Nepal has amended the policy for supportive staff in Nepal. The healthcare waste handlers are also grade-less staff for government hospitals. However, the local management committee of government hospitals has a provision to hire supportive staff from their local income. It has increased the chance of low retention of healthcare waste handlers in hospitals. The numbers of trained healthcare waste handlers in hospitals were not properly found. The majority of hospitals have no proper mechanism to treat and store healthcare waste before deposing the healthcare waste. Most of the hospitals do not have enough healthcare waste, and many healthcare waste handlers were not motivated to work due to low payments from the hospital. Conclusion: There is a need to enforce the legislation on healthcare waste management. In addition, regular training on healthcare waste management for healthcare waste handlers in healthcare facilities is required to improve the use and implementation of Healthcare Waste Management Guidelines 2014, Nepal.